Congenital genu recurvatum with dislocation of knee: A case report - Kalawar, Rosan Prasad Shah; Chaudhary, Shipra; Kalam, Abul; Sitoula, Prakash; Jha, Ranjiv; Shah, Sanjaya (Journal of Nobel Medical College, 2012)
A baby girl was born with severe deformity of left knee. Clinically and radiologically she was diagnosed as congenital dislocation of left knee. Gentle manipulation followed by above knee POP slab corrected the deformity in three weeks. A follow up at the age of 6 months showed normal position and range of motion of the knee. We are reporting this case for its rarity. Early recognition requires simple intervention only. DOI: http://dx.doi.org/10.3126/jonmc.v1i1.7291 Journal of Nobel Medical College Vol.1(1) 2011 68-70